Altered functional connectivity and spatiotemporal dynamics in individuals with central disorders of hypersomnolence - Daley, Lauren; Saini, Prabhjyot; Watters, Harrison; Bassil, Yasmine; Schumacher, Eric H.; Trotti, Lynn Marie; Keilholz, Shella (Frontiers in Neuroscience, 2025)
IntroductionIdiopathic hypersomnia (IH) is a sleep disorder characterized by highly disruptive symptoms. Like narcolepsy type 1, a well-characterized sleep disorder, individuals with IH suffer from excessive daytime sleepiness, though there is little overlap in metabolic or neural biomarkers across these two disorders. This lack of common pathophysiology, combined with the clear overlap in symptoms presents an ideal paradigm for better understanding the impact of IH on an individual’s functional activity and organization, and potentially, the underlying pathophysiology.MethodsThis study examines the observed functional connectivity in patients with IH, and patients with narcolepsy type 1 (NT1) against healthy control individuals. Static functional connectivity is compared, as are quasi-periodic patterns, acquired from the BOLD timecourse, for all groups. In addition to baseline data comparison, the study also included a post-nap condition, where the individuals included in this analysis napped for at least 10 min prior to the scanning session, to explore why individuals with IH do not feel “refreshed” after a nap like individuals with NT1 do.ResultsAssessing the groups’ spatiotemporal patterns revealed key differences across both disorders and conditions: static connectivity revealed at baseline higher subcortical connectivity in the NT1 group. There was also observably less connectivity in the IH group both at baseline and post-nap, though none of these static analyses survived multiple comparisons correction to reach significance. The quasi-periodic pattern (QPP) results however found significant differences in the IH group in key networks, particularly the DAN/FPCN correlation is significantly different at baseline vs. post-nap, a trend not observed in either the control or NT1 groups.ConclusionThe DAN and FPCN (task-positive correlates) are drastically altered both at baseline and post-nap when compared to the other groups, and may likely be a disorder-specific result. This study demonstrates that key networks for arousal are more heavily disrupted in IH patients, who are less affected by a nap, confirmed through both subject reporting and functional evidence through spatiotemporal patterns.